2013
DOI: 10.1177/1933719113483011
|View full text |Cite
|
Sign up to set email alerts
|

Placental Syncytiotrophoblast Maintains a Specific Type of Glycocalyx at the Fetomaternal Border: The Glycocalyx at the Fetomaternal Interface in Healthy Women and Patients With HELLP Syndrome

Abstract: Recent studies showed that considerable amounts of glycosaminoglycans are released into maternal blood during normal pregnancy and in hemolysis, elevated liver enzymes, and low platelets (HELLP) syndrome. Maternal endothelia and the syncytiotrophoblast layer have been discussed as a possible origin of these glycocalyx components. Our study aimed to visualize the glycocalyx on the syncytiotrophoblast by electron microscopy, to analyze its structure and composition by immunohistochemistry, and to determine poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Hoffman-Kiefer et al demonstrated that HS chain fragments, a major component of the placental glycocalyx, were increased in the circulation of women with HELLP syndrome (Hemolysis, Elevated Liver enzymes, and Low Platelet count), often considered an acute stage and extremely severe relative of preeclampsia [19,20]. Additional studies have demonstrated the importance of the HS chains in normal pregnancy to regulate sFLT-1 localization in the placenta [11].…”
Section: Discussionmentioning
confidence: 99%
“…Hoffman-Kiefer et al demonstrated that HS chain fragments, a major component of the placental glycocalyx, were increased in the circulation of women with HELLP syndrome (Hemolysis, Elevated Liver enzymes, and Low Platelet count), often considered an acute stage and extremely severe relative of preeclampsia [19,20]. Additional studies have demonstrated the importance of the HS chains in normal pregnancy to regulate sFLT-1 localization in the placenta [11].…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence of an elevated level of HA in the blood in the PE [64, 65] and HELLP syndromes [66]. The level of antibodies to HA and its structural disaccharide are also elevated in PE [67, 68].…”
Section: Regulatory Effect Of Ha Polymers Of Various Sizesmentioning
confidence: 99%
“…The surface of eukaryotic cells has a hydrated matrix of specialized proteoglycans and glycoproteins, linked to the plasma membrane, known as the glycocalyx [ 3 , 4 ] The vascular endothelial glycocalyx is a critical regulator of vascular function, and endothelial glycocalyx damage has been implicated in reperfusion oxidative injury, inflammation, atherosclerosis and diabetes [ 3 , 5 10 ]. The syncytiotrophoblast microvillous membrane surface also has a substantial glycocalyx [ 11 13 ] but its functions are poorly understood.…”
Section: Introductionmentioning
confidence: 99%